Genetic screening of children with marrow failure. The role of primary Immunodeficiencies. Issue 9 (2nd June 2021) - Miano, Maurizio; Grossi, Alice; Dell'Orso, Gianluca; Lanciotti, Marina; Fioredda, Francesca; Palmisani, Elena; Lanza, Tiziana; Guardo, Daniela; Beccaria, Andrea; Ravera, Silvia; Cossu, Vanessa; Terranova, Paola; et al.
Abstract: The differential diagnosis of marrow failure (MF) is crucial in the diagnostic work‐up, since genetic forms require specific care. We retrospectively studied all patients with single/multi‐lineage MF evaluated in a single‐center to identify the type and incidence of underlying molecular defects. The diepoxybutane test was used to screen Fanconi Anemia. Other congenital MFs have been searched using Sanger and/or Next Generation Sequencing analysis, depending on the available tools over the years. Between 2009–2019, 97 patients (aged 0–32 years‐median 5) with single‐lineage (29%) or multilineage (68%) MF were evaluated. Fifty‐three (54%) and 28 (29%) were diagnosed with acquired and congenital MF, respectively. The remaining 16 (17%), with trilinear (n=9) and monolinear (n=7) MF, were found to have an underlying primary immunodeficiency (PID) and showed clinical and biochemical signs of immune‐dysregulation in 10/16 (62%) and in 14/16 (87%) of cases, respectively. Clinical signs were also found in 22/53 (41%) and 8/28 (28%) patients with idiopathic and classical cMF, respectively. Eight out of 16 PIDs patients were successfully transplanted, four received immunosuppression, two did not require treatment, and the remaining two died. We show that patients with single/multi‐lineage MF may have underlying PIDs in a considerable number of cases and that MF may represent a relevant clinical sign in patients with PIDs, thus widening their clinical phenotype. An accurate immunological work‐up should be performed in all patients with MF, and PID‐related genes should be considered when screening MF in order to identify disorders that may receive targeted treatments and/or appropriate conditioning regimens before transplant.